Rhythm dynamics of the aging heart: an experimental study using conscious, restrained mice - Comelli, Martina (Am J Physiol Heart Circ Physiol, 2020)
Heart rate variability (HRV) is a measure of variation in time interval between heartbeats and reflects the influence of autonomic nervous system and circulating/locally released factors on sinoatrial node discharge. Here, we tested whether electrocardiograms (ECGs) obtained in conscious, restrained mice, a condition that affects sympathovagal balance, reveal alterations of heart rhythm dynamics with aging. Moreover, based on emergence of sodium channels as modulators of pacemaker activity, we addressed consequences of altered sodium channels on heart rhythm. C57Bl/6 mice and mice with enhanced late sodium current due to Nav1.5 mutation at Ser571 (S571E) at ~4 to ~24 mo of age, were studied. HRV was assessed using time- and frequency-domain and nonlinear parameters. For C57Bl/6 and S571E mice, standard deviation of RR intervals (SDRR), total power of RR interval variation, and nonlinear standard deviation 2 (SD2) were maximal at ~4 mo and decreased at ~18 and ~24 mo, together with attenuation of indexes of sympathovagal balance. Modulation of sympathetic and/or parasympathetic divisions revealed attenuation of autonomic tone at ~24 mo. At ~4 mo, S571E mice presented lower heart rate and higher SDRR, total power, and SD2 with respect to C57Bl/6, properties reversed by late sodium current inhibition. At ~24 mo, heart rate decreased in C57Bl/6 but increased in S571E, a condition preserved after autonomic blockade. Collectively, our data indicate that aging is associated with reduced HRV. Moreover, sodium channel function conditions heart rate and its age-related adaptations, but does not interfere with HRV decline occurring with age. NEW & NOTEWORTHY We have investigated age-associated alterations of heart rate properties in mice using conscious electrocardiographic recordings. Our findings support the notion that aging is coupled with altered sympathovagal balance with consequences on heart rate variability. Moreover, by using a genetically engineered mouse line, we provide evidence that sodium channels modulate heart rate and its age-related adaptations.